Physical Activity And Nurses’ Attribute Variables To Body Mass Index And Uric Acid - Ernawati Siagian; Putri Agape Ramschie (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2021)
Introduction: Obesity among health workers hinder the effectiveness of health promotion, harm their health, and reduce productivity in the workplace. Objective: The purpose of this study is to describe the attribute variables, daily activity patterns, BMI and uric acid levels in nurses. Methods: The method in this study is a descriptive correlational using purposive sampling technique, amounting 50 respondents. International Physical Activity Questionnaire (IPAQ) was used for the physical activity data, BMI and checking uric acid levels. Results: The results showed Obese I BMI (58%), Obese II BMI (42%), Prediabetes fasting blood sugar levels (28%), Diabetes (4%). Moderate physical activity patterns is 80% METs- mins/week. Analysis showed that there is a significant relationship between age and physical activity patterns (METs- mins/week) with p value of 0,02<0,05. There is a significant relationship between marital status and physical activity patterns with p value of 0,005. There is also a significant relationship between chronic disease and uric acid levels with p value of 0,020<0,05. There is no significant relationship between BMI and uric acid levels with physical activity patterns (sig>0,05). Conclusion: Obesity among professional nurses has negative implications for the capacity, success, follow-up and safety of health services and the health of these nurses. Nurses need to achieve and maintain a healthy body weight.